Penerapan metode cost plus pricing berbasis full costing dalam penentuan harga jual jual pada Pabrik Tahu Triple S - Artika, Riska; Alexander, Stanly W.; Latjandu, Lady Diana (Manajemen Bisnis dan Keuangan Korporat, 2025)
Cost-plus pricing is a method for determining the selling price by adding the total production cost incurred during the manufacturing process and applying a markup percentage, which is calculated based on the company's return on investment. The selling price plays a crucial role in ensuring a company's sustainability. This study aims to analyze the determination of product selling prices using the cost-plus pricing method by calculating the cost of production through the full costing method at the Triple S Tofu Factory in Kleak, Manado Village. This research employs a qualitative approach. The findings indicate that the selling prices set by the company are higher than those calculated using the cost-plus pricing method. The company's selling price for small tofu is IDR 300 and for large tofu is IDR 400, whereas the selling price determined using the cost-plus pricing method is IDR 400 for small tofu and IDR 506 for large tofu.